Association Between Climatic Factors and Malaria Incidence in Papua, Indonesia - Ashar, Yulia Khairina; Safira , Putri; Lauchan, Agil Maritho (Gema Lingkungan Kesehatan, 2025)
Malaria remains a major public health concern in many countries, including Indonesia, particularly in endemic regions such as Papua. The province of Papua records the highest number of malaria cases, contributing approximately 92% of the national burden. Fluctuations in morbidity and mortality rates due to malaria in this region underscore the urgency of targeted control measures. Several environmental and climatic factors are believed to influence malaria transmission, yet comprehensive analyses in Papua remain limited. This study aimed to determine the relationship between climatic factors and the incidence of malaria in Papua.This type of research is descriptive observational with ecological study design. The data source was secondary data from the Indonesian Health Survey for malaria cases and the Meteorology Climatology and Geophysics Agency (BKMG) for climate factor data. Based on the results showed that Rainfall (p=0.187; r=-0.445), humidity (p=0.627, r=-0.176), temperature (p=0.091, r=0.802), wind speed (p=0.004, r=0.818), and duration of sunshine (p=0.038, r=0.661). Findings suggest that wind speed and solar irradiation are significant predictors of malaria incidence, thus environmental management strategies should consider consider thes variables.